DEVELOPMENT OF ENRICHED VIRTUAL CLASSROOM WITH PEDATI IN CONSTRUCTION COST ESTIMATE COURSE - Riza Nur Dwi Lutfiana; Dika Arya Yasa; Eveline Siregar (LPPM Universitas Negeri Jakarta, 2023)
This study aims to develop designs and learning products for the Enriched Virtual Classroom using PEDATI in building construction planning. Enriched Virtual Classroom belongs to blended learning. This learning model is one of the models where the learning process is played with technology and face-to-face learning is only an additional supplement if needed. The development procedure uses the ADDIE model which is integrated with the PEDATI model at the learning design preparation stage. The components and indicators for the expert review of the instrument were prepared based on the standard components and indicators of the